Schisandrin B Induced ROS-Mediated Autophagy and Th1/Th2 Imbalance via Selenoproteins in Hepa1-6 Cells - Tan, Siran; Zheng, Zhi; Liu, Tianqi; Yao, Xiaoyun; Yu, Miao; Ji, Yubin (Frontiers in Immunology, 2022)
Schisandrin B (Sch B) is well-known for its anti-tumor effect, however, its underlying mechanism remains confusing. The aim of our study was to investigate the role of selenoproteins in Sch B induced autophagy and Th1/Th2 imbalance in hepa1-6 cells. Hepa1-6 cells were chosen to explore the anti-tumor mechanism and were treated with 0, 25,50, 100μM of Sch B for 24h, respectively. We detected the inhibition rate of proliferation, transmission electron microscopy (TEM), MDC staining, ROS level and oxidative stress-related indicators, autophagy-related genes, related Th1/Th2 cytokines and selenoproteins mRNA expressions. Moreover, the heat map, principal component analysis and correlation analysis were used for further bioinformatics analysis. The results revealed that Sch B exhibited well-inhibited effects on hepa1-6 cells. Subsequently, under Sch B treatment, typical autophagy characteristics increasingly apparent, the level of punctate MDC staining enhanced and regulated the autophagy-related genes, overall, Sch B induced autophagy in hepa1-6 cells. In addition, Sch B promoted ROS accumulation eventually triggered autophagy initiation. Results of Th1 and Th2 cytokines mRNA expressions indicated that Th1/Th2 immune imbalance observed by Sch B treatment in hepa1-6 cells. Intriguingly, Sch B down-regulated majority of selenoproteins expression. Also, the heat map results observed significant variation of autophagy-related genes, related Th1/Th2 cytokines and selenoproteins expressions in response to Sch B treated. PCA outcome suggested the key role of Txnrd1, Txnrd3, Selp, GPX2, Dio3, Selr with its potential interactions in ROS-mediated autophagy and Th1/Th2 imbalance of hepa1-6 cells. In conclusion, Sch B induced ROS-mediated autophagy and Th1/Th2 imbalance in hepa1-6 cells. More importantly, majority of selenoproteins were intimately involved in the process of autophagy as well as Th1/Th2 imbalance, Txnrd3, Selp, GPX2, Dio3, Selr had considerable impact on the process.